Linking maternal psychological state and infant problem behavior - Čekuolienė, D.; Jusienė, R.; Širvinskienė, G.; Zamalijeva, O.; Breidokienė, R. (Psichologija, 2011)
The influence of maternal psychological state and emotional well-being on the child’s development is undeniable. Studies have documented an association of maternal depression during pregnancy and postpartum periods with several aspects of adverse infants’ development. Maternal depression is also considered to be a risk factor for individual psychopathology later in life. However, identifying the variables qualifying maternal psychological state and analyzing their complex relations with children problem behavior continues to be a challenging research assignment for psychologists. The main goal of the present study was to examine the manifold relations among the different indices of maternal psychological state and infants’ problem behavior. Participants of the study1 were 202 mothers and their full-term infants. Mothers completed several self-report questionnaires three times: on the 2nd/3rd day after delivery, and when the infants were three months and six months old. The women’s perception of the infant’s difficult behaviors scale (Bornstein et al., 2006) was used when infants were three and six months old. Maternal depression was measured with the Edinburgh postnatal depression scale (Cox et al., 1987) in all three stages of the study. Results: Maternal depressiveness appeared to be the most important aspect of maternal psychological state, strongly linked to the infants’ problem behavior. The data have shown that maternal depressiveness and the quality of relationships with the husband / partner influenced the infants’ behavior through maternal difficulties to understand the reason for the infant’s crying. Maternal depressiveness during the postpartum period and the quality of relationship with the husband / partner has an indirect impact on the infant’s problem behavior, i.e. depressiveness affects the maternal understanding of infant’s crying, and the quality of relationship with the husband / partner has an impact on maternal depressiveness in the postpartum period. The results of structural equation modeling indicate that maternal ability to understand infant crying is the only significant variable having a direct effect on infants’ problem behavior, i.e. difficulties to understand the reasons for the infant’s crying influence the quantity of manifestation of infants’ behavior problems at the age of three and six months. A group comparison has demonstrated that single and lower educated mothers reported significantly more cases of infants’ problem behavior. These results support the theoretical premises and empirical findings that maternal psychological state determines infants’ problem behavior through the mother’s emotional well-being which is closely linked to the family structure and relationship quality.